EKSPERIMENTASI PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK (PMR) DAN OPEN ENDED PADA MATERI SEGITIGA DAN SEGIEMPAT DITINJAU DARI GAYA KOGNITIF SISWA KELAS VII SMP NEGERI SE-KABUPATEN PACITAN - Putra, Aji Permana; Riyadi, Riyadi; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objectives of this research were to find out on  the topic of circumference and area of triangles and quadrangles: (1) which one produce better learning achievement among Realistic Mathematics Education (RME) approach, open ended approach or a mechanistic approach; (2) which had better learning achievement between field dependent cognitive style students or field independent cognitive style students; (3) at each cognitive styles, which was better learning achievement among RME approach, open ended approach or mechanistic approach, and (4) at each learning approach, which had better learning achievement between field dependent cognitive style students or field independent cognitive style students. This research was a quasi-experimental with 3×2 factorial design. The population was all students in seventh grade of state Junior High School in Pacitan Regency on Academic Years 2012/2013. Sampling was done by stratified cluster random sampling technique. The total of sample was 238 students. Statistical tests using the method Lilliefors test for normality, homogeniety of the Bartlett method, anava test with F test (Fisher) and post hoc test using the Scheffe’ method. The significance level was 0,05. Based on hypothesis test, it could  be concluded that: (1) RME approach produce better learning achievement than open ended approach and mechanistic approach, open ended approach produce better learning achievement than mechanistic approach; (2) the field independent cognitive style students have a better learning achievement than field dependent cognitive style students; (3) at each of cognitive styles, RME approach produce better learning achievement than open ended approach and mechanistic approach, open ended approach produce better learning achievement than mechanistic approach; (4) at each learning approach, field independent cognitive style students have better learning achievement than field dependent cognitive style students.Keywords: Field Dependent, Field Independent, Mechanistic, Open Ended, Realistic Mathematics Education (RME).